The Use of Address Terms by Thomas Shelby as the Main Character in Peaky Blinders - Livia Ester (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This research seeks to study the use of address terms in a business talk. Address terms such as FN, LN, T, TLN, KT, PN, or Miscellaneous, are selectively used to address others depending on some social factors such as age, gender, social occasions, social relationship, family relationship, occupational hierarchy, as well as racial background. This research studies qualitatively the utterances of Thomas Shelby, the main character in Peaky Blinders. The findings show that Thomas Shelby only uses FN, TLN, and Miscellaneous, such as person deixis and zero address term. Therefore, in a business talk, a speaker may choose the use of appropriate terms of address in accordance with the social factors to maximize communication’s purposes.